Mathematical Model of Criterion Assessment - Kovtunets, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
Mathematical model of criterion assessment of learning outcomes developed to study subject validity of assessment.